The Textual Features In Persuading Student on School Advertisement: A Textual Analysis - Rahmah, Neneng Farida; Nurfithri, Nurfithri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research focuses on the textual features used in persuading Student in the school advertisement: A Discourse study. Those strategies can be analyzed by a discourse study to find what kind of textual features used in the advertisement and what the function of those features. This research employs descriptive qualitative method by which the researcher categories, describes, and analyzes. The researcher uses the theory of textual analysis (Fairclough, 2003), discourse of advertising (Cook, 1992) and some supporting theories to solve the problem presented in the research questions. The data used in this research are taken from the Masdrasah Aliyah in Bandung Regency. There are 25 school advertisement that are heading the Madrasah Aliyah. The finding shows that there are five textual features that have been analyzed. They are the use of pronoun ‘you, your’, and ‘we’, our’ that is to establish a certain type of correlation between the student as a reader and the advertiser. In term of grammatical mood, there are 3 kinds of sentences. The imperative is the most used. This means building a close relationship between readers and advertisers by persuading readers to take an action such buy the product. In the grammatical feature, the product uses the positive adjective that highlights the positive effects in quality of product, while only twice the advertisers use the negative adjectives to connect to the problems which existed prior to using the products. In modality, there are two kinds of modals used in this product, they are ‘will’ that means the commitment to act, and ‘can’ that means the commitment of ability. Last, the researcher finds that the product uses the sense of causal means problem-solving that motivates Student to ‘buy product’ by providing reasons.